A very unusual complication of amniocentesis. Issue 6 (12th March 2015) - Hayat, Munawar; Hill, Michael; Kelly, David; Tubbs, R. Shane; Loukas, Marios
Key Clinical Message The uses of amniocentesis are numerous, including determination of chromosomal abnormalities, lung maturity, and infections. A common complication of amniocentesis is loss of the pregnancy, but rare complications should be considered. The role of patient history and clinical observation of uncommon presentations are critical in the management of the patient.